2019
DOI: 10.1007/s40140-019-00357-6
|View full text |Cite
|
Sign up to set email alerts
|

You Are Only as Frail as Your Arteries: Prehabilitation of Elderly Surgical Patients

Abstract: Purpose of Review To discuss the concept of prehabilitation for the elderly frail surgical patient as well as strategies to improve preoperative functional capacity and vascular function to decrease postoperative complications. Recent Findings Frailty is associated with poor surgical outcomes yet there is no consensus on how frailty should be measured or mitigated in the preoperative period. Prehabilitation, or improving functional capacity prior to surgery typically through exercise, has been shown to be an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“… n.a. Colorectal cancer Colorectal cancer surgery Not defined Not defined Durand et al [ 40 ] Review article n.a. n.a.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… n.a. Colorectal cancer Colorectal cancer surgery Not defined Not defined Durand et al [ 40 ] Review article n.a. n.a.…”
Section: Resultsmentioning
confidence: 99%
“…Six documents did not report their funding and potential conflict of interest and should be considered with caution [ 32 , 35 , 39 , 41 , 62 , 63 ]. Eleven documents, which either did not report a conflict of interest or reported no conflict of interest, received research grants or sponsoring by different national research institutions (non-profit funding), whereas seven documents reported a combination of “none” and “not reported” for conflict of interest and funding [ 21 , 36 , 40 , 46 , 50 , 59 , 60 ]. Four other documents declared a conflict of interest, including a CEO position in a firm providing services used in the study [ 58 ], a consulting position and intellectual property ownership [ 47 ], and financial contributions by medical firms unrelated to the research [ 34 , 37 ].…”
Section: Resultsmentioning
confidence: 99%